'African gangs' in Australia: Perceptions of race and crime in urban neighbourhoods. Issue 2 (June 2021) - Benier, Kathryn; Wickes, Rebecca; Moran, Claire
In 2016, Melbourne experienced what was referred to in the media as the Moomba 'riot'. This event led to a racialised political and media campaign regarding the problem of 'African gangs'. Despite no evidence of actual gang activity, the backlash against black migrants in Melbourne was consequential with increases in reported racism and institutionalised forms of discrimination. In this study, we examine the neighbourhood context of exclusion against African Australians following the Moomba 'riot'. Using census and crime data integrated with survey data from 2400 residents living in 150 urban neighbourhoods, we interrogate the relationship between sentiments (measured as anger) towards Africans and perceptions of neighbourhood crime and disorder. We further consider whether quality contact with Africans and neighbourhood cohesion mediates this relationship. We conclude with reflections on the significant and deleterious effects of the 'black and criminal' association on understandings of 'Africanness' in Australia.